![\bf y=a(b)^x\qquad \qquad (\stackrel{x}{0}~,~\stackrel{y}{3})\implies 3=a(b)^0\implies 3=a \\\\\\ therefore\qquad y=3(b)^x\\\\ -------------------------------\\\\ (\stackrel{x}{1}~,~\stackrel{y}{6})\implies 6=3(b)^1\implies \cfrac{6}{3}=b^1\implies 2=b \\\\\\ therefore\qquad y=3(2)^x](https://tex.z-dn.net/?f=%5Cbf%20y%3Da%28b%29%5Ex%5Cqquad%20%5Cqquad%20%28%5Cstackrel%7Bx%7D%7B0%7D~%2C~%5Cstackrel%7By%7D%7B3%7D%29%5Cimplies%203%3Da%28b%29%5E0%5Cimplies%203%3Da%0A%5C%5C%5C%5C%5C%5C%0Atherefore%5Cqquad%20y%3D3%28b%29%5Ex%5C%5C%5C%5C%0A-------------------------------%5C%5C%5C%5C%0A%28%5Cstackrel%7Bx%7D%7B1%7D~%2C~%5Cstackrel%7By%7D%7B6%7D%29%5Cimplies%206%3D3%28b%29%5E1%5Cimplies%20%5Ccfrac%7B6%7D%7B3%7D%3Db%5E1%5Cimplies%202%3Db%0A%5C%5C%5C%5C%5C%5C%0Atherefore%5Cqquad%20y%3D3%282%29%5Ex)
now, exponential functions have a horizontal asymptote at the x-axis, namely when y = 0, however, if you just move this one with a vertical translation of 2, then the horizontal asymptote will be at 2 instead.
y = 3(2)ˣ + 2
It is these nuts go chu now do your own homework
The values of cosine Ф and cotangent Ф are
and -1
Step-by-step explanation:
When a terminal side of an angle intersect the unit circle at
point (x , y), then:
- The x-coordinate is equal to cosine the angle between the positive part of x-axis and the terminal side
- The y-coordinate is equal to sine the angle between the positive part of x-axis and the terminal side
- If x and y coordinates are positive, then the angle lies in the 1st quadrant
- If x-coordinate is negative and y-coordinate is positive, then the angle lies in the 2nd quadrant
- If x and y coordinates are negative, then the angle lies in the 3rd quadrant
- If x-coordinate is positive and y-coordinate is negative, then the angle lies in the 4th quadrant
∵ The terminal ray of angle Ф intersects the unit circle at point ![(\frac{-\sqrt{2} }{2},\frac{\sqrt{2} }{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B-%5Csqrt%7B2%7D%20%7D%7B2%7D%2C%5Cfrac%7B%5Csqrt%7B2%7D%20%7D%7B2%7D%29)
- According to the 1st and 2nd notes above
∴ cosФ = x-coordinate of the point
∴ sinФ = y-coordinate of the point
∵ The x-coordinate of the point is negative
∵ They-coordinate of the point is positive
- According the the 4th note above
∴ Angle Ф lies in the 2nd quadrant
∵ x-coordinate = ![\frac{-\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-%5Csqrt%7B2%7D%20%7D%7B2%7D)
∴ cosФ = ![\frac{-\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-%5Csqrt%7B2%7D%20%7D%7B2%7D)
∵ y-coordinate = ![\frac{\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B2%7D%20%7D%7B2%7D)
∴ sinФ = ![\frac{\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B2%7D%20%7D%7B2%7D)
- cotФ is the reciprocal of tanФ
∵ tanФ = sinФ ÷ cosФ
∴ cotФ = cosФ ÷ sinФ
∴ cotФ =
÷ ![\frac{\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B2%7D%20%7D%7B2%7D)
∴ cotФ = -1
The values of cosine Ф and cotangent Ф are
and -1
Learn more:
You can learn more about the trigonometry function in brainly.com/question/4924817
#LearnwithBrainly
identity property=something times one
Answer:
D.
Step-by-step explanation: